Pengaruh Kualitas Produk, Kepuasan Konsumen, dan Competitive Advantage terhadap Keputusan Pembelian Pada PT. Sejahtera Motor Gemilang Medan - Hendra Jonathan Sibarani; Nada Lovina Br Pangaribuan; Andri Putra Pranata Ginting; Erikson Albertus Simanjorang (Ekonomis: Journal of Economics and Business, 2020)
Purchasing decision are conscious consumer desire to choose a product among the available alternative actions. Purchasing decisions in this researcher are influenced by product quality, customer satisfaction, and competitive advantage. The population in this study were 295 consumers using the Slovin formula and obtained a sample of 170 consumers. Product quality variables partially and simultaneously have a positive and significant effect on purchasing decision variables by using the comparison tcount> ttable and Fcount>Ftable. Partial and simultaneous consumer satisfaction variables have no positive and insignificant effect on purchasing decisions by using the comparison tcount <ttable and Fcount> Ftabel. The competitive advantage variable partially and simultaneously has no and significant effect on purchasing decisions by using the comparison tcount <ttable and Fcount <Ftabel.